The Vascular Consequences of Metabolic Syndrome: Rodent Models, Endothelial Dysfunction, and Current Therapies - Tran, Vivian; De Silva, T. Michael; Sobey, Christopher G.; Lim, Kyungjoon; Drummond, Grant R.; Vinh, Antony; Jelinic, Maria (Frontiers in Pharmacology, 2020)
Metabolic syndrome is characterized by visceral obesity, dyslipidemia, hyperglycemia and hypertension, and affects over one billion people. Independently, the components of metabolic syndrome each have the potential to affect the endothelium to cause vascular dysfunction and disrupt vascular homeostasis. Rodent models of metabolic syndrome have significantly advanced our understanding of this multifactorial condition. In this mini-review we compare the currently available rodent models of metabolic syndrome and consider their limitations. We also discuss the numerous mechanisms by which metabolic abnormalities cause endothelial dysfunction and highlight some common pathophysiologies including reduced nitric oxide production, increased reactive oxygen species and increased production of vasoconstrictors. Additionally, we explore some of the current therapeutics for the comorbidities of metabolic syndrome and consider how these benefit the vasculature.